Institutional change of accounting systems : the adoption of a regime of adapted International Financial Reporting Standards - Guerreiro, Marta Alexandra Silva (2015)
This study combines Dillard et al.’s (2004) institutional change model with institutional entrepreneurship theory. The aim is to enhance understanding of institutional change processes when a country adopts international accounting standards. For empirical support, we focus on the changes in social structures and accounting practices that arose in 2010 when Portugal replaced its national accounting system for unlisted companies, with a new system of accounting based on International Financial Reporting Standards. We reveal how an evolving socio-economic and political context, and the embedding of central actors in multiple fields, facilitated entrepreneurial action by actors who took political opportunity, mobilized important allies, and accommodated the interests of major protagonists. We draw attention to the possibility of an earlier inversion of the cascading institutionalization process than is envisaged by Dillard et al. (2004). At the organizational field level, we highlight how national professional accounting associations and business associations can shape criteria established at the political and economic level, thereby counteracting the institutionalization process. At the organizational level, we focus on the accounting standard for small and medium sized entities. We provide insights to why some accountants maintained structures of meaning associated with the previous accounting system.